2020
DOI: 10.3390/jcm9103293
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, Treatment Response and Short-Term Outcomes in Paediatric Multisystem Inflammatory Syndrome Temporally Associated with SARS-CoV-2 (PIMS-TS)

Abstract: The novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the pathogen responsible for Coronavirus Disease 2019 (COVID-19). Whilst most children and young people develop mild symptoms, recent reports suggest a novel paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS). Case definition and classification are preliminary, treatment is empiric and disease-associated outcomes are unclear. Here, we report 29 patients with PIMS-TS who were diagnosed, admitted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 78 publications
5
91
0
8
Order By: Relevance
“…When focusing on severe abdominal manifestations, we found nine patients affected by MIS-C who underwent exploratory laparotomies: two children with a healthy appendix as finding (“pseudo appendicular syndrome”) [ 16 , 17 ], one with aseptic peritonitis [ 18 ], four with appendicitis [ 19 ] and two with mesenteric lymphadenitis [ 20 ]. Appendicitis was initially suspected in roughly 5–30% [ 16 , 18 , [20] , [21] , [22] , [23] , [24] ] of the reviewed case series and in four case reports [ 9 , 17 , 25 , 26 ]. Three patients underwent intestinal resection with re-anastomosis due to segmental inflammation with necrosis of terminal ileum [ 9 , 17 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When focusing on severe abdominal manifestations, we found nine patients affected by MIS-C who underwent exploratory laparotomies: two children with a healthy appendix as finding (“pseudo appendicular syndrome”) [ 16 , 17 ], one with aseptic peritonitis [ 18 ], four with appendicitis [ 19 ] and two with mesenteric lymphadenitis [ 20 ]. Appendicitis was initially suspected in roughly 5–30% [ 16 , 18 , [20] , [21] , [22] , [23] , [24] ] of the reviewed case series and in four case reports [ 9 , 17 , 25 , 26 ]. Three patients underwent intestinal resection with re-anastomosis due to segmental inflammation with necrosis of terminal ileum [ 9 , 17 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several authors reported acute abdomen presentation in a not negligible number of patients. Our systematic review of literature evidenced acute abdomen presentation up to 30% [ 16 , 18 , [20] , [21] , [22] , [23] , [24] ]. It is attractive to speculate that vascular damage could probably play a role as well with this regard.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] In addition, COVID-19 infection can lead to multi inflammatory syndrome in children (MIS C) and there is some evidence that children may experience long COVID with ongoing symptoms, including fatigue and pain. [7][8][9] Preventing COVID-19 in children is of critical importance and, to date, mask wearing and social distancing, including closing or reducing time at school, have been the primary approaches for infection control. 10,11 While no COVID-19 vaccines are yet approved for children <16 years of age, clinical trials in pediatric populations are underway.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in case of fulfillment of other criteria necessary, diagnosis might be made more often. Since the first description of this syndrome, numerous cases have been published worldwide [ 16 , 17 , 18 ], sometimes leading to harmful disease or even death. Early recognition of this entity is important since early therapy can prevent a catastrophic course of the disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%